2016
DOI: 10.17221/330/2014-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lupin seed supplementation on egg production performance, and qualitative egg traits in laying hens

Abstract: ABSTRACT:We investigated the effects of lupin (Lupinus angustifolius L.) seed supplementation on egg production performance and egg quality in laying hens. A total of 120 Hy-Line Brown laying hens (29-week old) were used in a nine week trial. Laying hens were sorted into pens with six birds per pen and five pens per treatment. Treatments were (1) control, corn-soybean meal-based control diets, (2) 11% lupin (control + 11% lupin), (3) 16.5% lupin (control + 16.5% lupin), and (4) 22% lupin (control + 22% lupin).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
2
8
0
2
Order By: Relevance
“…Laudadio and Tufarelli [37] used dehulled L. albus seed in the amount of 180 g/kg in laying hen diets and reported that the performance (body weight at the end of the experiment, feed conversion kg of feed/kg egg, laying rate, and egg weight) was similar to that obtained for the hens from the group without lupine. The results obtained by the quails that received whole lupine seeds in a proportion of 20% in the feed are in agreement with the findings of Park et al [73], who showed that blue lupine seeds utilization up to 22% in the diet of laying hens provided an even higher egg production than hens that received only soybean meal. Other research, in accordance with our data, also showed that positive performance was obtained for laying hens in terms of body weight, feed intake, egg production (%), and feed conversion ratio (kg feed/kg egg mass and kg feed/dozen egg) when whole blue lupine [19,20,74] or yellow lupine [60] seeds were included in the feed structure up to 20%.…”
Section: Performance Responses Of Quailssupporting
confidence: 92%
See 1 more Smart Citation
“…Laudadio and Tufarelli [37] used dehulled L. albus seed in the amount of 180 g/kg in laying hen diets and reported that the performance (body weight at the end of the experiment, feed conversion kg of feed/kg egg, laying rate, and egg weight) was similar to that obtained for the hens from the group without lupine. The results obtained by the quails that received whole lupine seeds in a proportion of 20% in the feed are in agreement with the findings of Park et al [73], who showed that blue lupine seeds utilization up to 22% in the diet of laying hens provided an even higher egg production than hens that received only soybean meal. Other research, in accordance with our data, also showed that positive performance was obtained for laying hens in terms of body weight, feed intake, egg production (%), and feed conversion ratio (kg feed/kg egg mass and kg feed/dozen egg) when whole blue lupine [19,20,74] or yellow lupine [60] seeds were included in the feed structure up to 20%.…”
Section: Performance Responses Of Quailssupporting
confidence: 92%
“…Previously, Hammershøj and Steenfeldt [85] showed that hen egg weight was significantly reduced when whole seeds of L. angustifolius were used at a dose of 250 g/kg in feed. However, some research has shown that eggs with an insignificant weight difference can be obtained when blue lupine seeds are used up to 22% in feed [19,73] and even 30% [60].…”
Section: Egg Quality Parametersmentioning
confidence: 99%
“…Egg weight was not found to be dependent on the age of the hens during the laying period (4–20 weeks). Similarly, Park et al [ 32 ] did not show a statistically significant effect of the laying period and diet on the egg weight of Hy-Line Brown hens. However, the relationship between egg weight and laying weeks (feeding phases) has been demonstrated in our own study with Rosa 1 laying hens.…”
Section: Discussionmentioning
confidence: 87%
“…Климатические условия Польши, Белоруссии и Германии благоприятны для возделывания узколистного и желтого люпина. Изучается его влияние на продуктивность и качество яиц птицы (10)(11)(12) при оптимизации рецептур рационов (13), эффекты антипитательных веществ (14), возможности применения низкоалкалоидных сортов (15), цельных и обрушенных семян (16). В Англии ведутся исследования по оценке кормовой ценности и перспектив использования голубого люпина (17,18).…”
unclassified
“…Кормовой люпин обычно содержит до 42 % протеина и служит хорошим источником пополнения комбикормов сырым протеином, что особенно важно при дефиците качественных животных кормов и соевого шрота. К недостаткам люпина относится высокое содержание клетчатки (12,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16),0 %) и лигнина (0,9 %), а также наличие алкалоидов (в сладких сортах люпина -0,008-0,120 %, в горьких -1-3 %). Алкалоиды люпиналупинин, люпанин, люпинин, спартеин и гидроксилюпанин.…”
unclassified